Effects of continuing nursing care under cognitive behavioral intervention on psychological state and living quality in patients with double J catheter after ureterolithiasis surgery - Mu, Nannan; Wu, Shuling; Wang, Hui; Chen, Shaona; Lu, Jiaxiang; Huang, Shaoqing; Fu, Xiaoli (American journal of translational research, 2021)
The effects of continuing nursing care under cognitive behavioral intervention on the psychological state and living quality of patients with double J catheter after ureterolithiasis surgery were analyzed in this research.OBJECTIVEThe effects of continuing nursing care under cognitive behavioral intervention on the psychological state and living quality of patients with double J catheter after ureterolithiasis surgery were analyzed in this research.The research subjects in this study were 142 patients who were discharged from our hospital with a double J tube after ureterolithiasis surgeries from June 2019 to June 2020. According to the patient care plan, the subjects were divided into the control group (n=71) and the observation group (n=71) and respectively treated with routine basic nursing measures and continuing nursing care under cognitive-behavior intervention. Subsequently, the psychological state, living quality and the complications that occurred were compared between the two groups.METHODSThe research subjects in this study were 142 patients who were discharged from our hospital with a double J tube after ureterolithiasis surgeries from June 2019 to June 2020. According to the patient care plan, the subjects were divided into the control group (n=71) and the observation group (n=71) and respectively treated with routine basic nursing measures and continuing nursing care under cognitive-behavior intervention. Subsequently, the psychological state, living quality and the complications that occurred were compared between the two groups.The depression and anxiety scores of the two groups after 4 weeks of intervention, comparing to thoes before intervention, were seen with remarkably decreased significance (P<0.05). The scores of living quality and self-care quality of patients in the observation group were obviously higher than those in the control group (P<0.05). In addition, the incidence of complications in the observation group was critically lower than that in control group (P<0.05).RESULTSThe depression and anxiety scores of the two groups after 4 weeks of intervention, comparing to thoes before intervention, were seen with remarkably decreased significance (P<0.05). The scores of living quality and self-care quality of patients in the observation group were obviously higher than those in the control group (P<0.05). In addition, the incidence of complications in the observation group was critically lower than that in control group (P<0.05).Continuous nursing care under cognitive behavioral intervention can substantially improve the psychological state, living quality and self-care ability of patients with double J tube after ureterolithiasis surgery, and reduce the incidence of complications, which is worthy of clinic promotion.CONCLUSIONContinuous nursing care under cognitive behavioral intervention can substantially improve the psychological state, living quality and self-care ability of patients with double J tube after ureterolithiasis surgery, and reduce the incidence of complications, which is worthy of clinic promotion.